Effect of varying warm-up intensities on intermittent sprint performance - Wallman, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Warm-up (WUP) is a well-accepted practice considered by many athletes to be an essential precursor to exercise. Physiologically, an active WUP is proposed to improve subsequent exercise performance as a result of numerous temperature and non-temperature related benefits (see reviews by Bishop, 2003a, Bishop 2003b). While a number of studies have investigated the effect of WUP on subsequent continuous exercise or single-sprint performance, few studies have assessed the effects of WUP, compared to no-WUP, on intermittent sprint performance, with results being equivocal (Bishop & Claudius, 2004; Mohr et al., 2004). Further, there has been minimal research that has assessed the effects of WUP on exercise where WUP intensities were based on individual lactate thresholds. Therefore the aim of this study was to investigate the effect of different WUP intensities, based on lactate accumulation, on 10-min of subsequent intermittent sprint performance, and to determine whether core temperature (Tc) correlated with performance. Methods: Eleven male, team-sport athletes performed four experimental trials in a randomised, Latin-square, cross-over design, each separated by one week, consisting of an intermittent sprint protocol (15 x 20 m sprints, separated by 30 or 60-s) that followed either no-WUP or one of three 10-min WUP trials. WUP intensities were performed at either (1) half the difference between anaerobic threshold (AT) and lactate threshold (LT) [(AT-LT)/2] below the LT level = WUP 1; (2) mid-way between LT and AT level = WUP 2; (3) half the difference between LT and AT, [(AT-LT)/2] above AT level = WUP 3. Results: Individual sprint times showed a significant main effect for sprints (p = 0.001) but not for trials (p = 0.434), with sprint 4 being faster than sprint 3 and sprints 4, 5, 7 and 10 being faster than sprint 12 (p < 0.05). Warm-up 3 resulted in faster individual sprint times for sprints 1, 2, 3, 5, 6, 8, 9, and 14 (Cohen`s d = 0.51 - 1.13), compared to WUP 1 and no-WUP, as well as faster accumulated sprint times for the entire 15-sprint protocol, with moderate to large effect sizes found for accumulated sprints 1 - 10 (d = 0.50 - 1.05). There were no significant correlations between Tc assessed immediately after each WUP and any performance variable. Conclusion: A WUP performed half the difference between LT and AT above AT (i.e., WUP 3) resulted in faster intermittent sprint performance compared to lower intensity WUPs and no-WUP. Significant increases in with Tc were not correlated with exercise performance.